2017
DOI: 10.1002/chem.201704932
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation on Resorcinarenes towards either Inhibiting or Promoting Insulin Fibrillation

Abstract: Different tail-engineered resorcinarenes have been examined for insulin fibrillation by experimental and computational studies. The resorcinarene showed a promising effect on the inhibition of insulin fibrillation, studied using a ThT assay, circular dichroism spectroscopy, and atomic force microscopy. Both the ThT assay and computational results indicate the tail from the resorcinarene has an impact on insulin fibrillation by either inhibition or promotion because of the resident position on insulin. These ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…More recently, the same research group studied the effects of different tail-engineered resorcinarenes on the aggregation of insulin. [75] The resorcinarene itself exerts a strong inhibitory effect on insulin at a ratio of 1:0.2 (insulin:resorcinarene). However, changing the tail from F I G U R E 6 Molecular structures of the calixarenes reported to modulate the aggregation of amyloid proteins thiomethyl to propyl or butyl results in disappearance of the inhibitory effect.…”
Section: Cas For Modulating Amyloid Aggregationmentioning
confidence: 99%
“…More recently, the same research group studied the effects of different tail-engineered resorcinarenes on the aggregation of insulin. [75] The resorcinarene itself exerts a strong inhibitory effect on insulin at a ratio of 1:0.2 (insulin:resorcinarene). However, changing the tail from F I G U R E 6 Molecular structures of the calixarenes reported to modulate the aggregation of amyloid proteins thiomethyl to propyl or butyl results in disappearance of the inhibitory effect.…”
Section: Cas For Modulating Amyloid Aggregationmentioning
confidence: 99%
“…[115] The investigation by Xu et al on resorcinarene, a polyphenolic cyclic oligomer, revealed its potential towards inhibiting insulin fibrillation and serves as a new strategy towards maintaining insulin stability. [120] Length of engineered tails of such resorcinarene derivatives play a pivotal role with respect to its inhibitory efficacy. Moreover, many reports have described the inhibitory efficacy of cyclodextrin in insulin fibrillation through electrostatic and hydrophobic interactions.…”
Section: Other Additivesmentioning
confidence: 99%
“…We then employed solid-state NMR to further confirm that GCA and CD were coassembled. Compared with GCA + CD, the benzene 13 C peak of GCA-CD underwent a downfield shift (Supporting Information Figure S2), thereby indicating that GCA interacted with CD in the GCA-CD coassembly. Having confirmed the formation of the GCA-CD coassembly, we validated whether these two kinds of macrocycles were evenly distributed on the surface of the coassembly or self-sorted each other to generate microphase separation by using energydispersive spectrometry-elemental mapping analysis.…”
Section: Construction and Characterization Of The Gca-cd Coassembly Of Heteromultivalent Recognitionmentioning
confidence: 99%
“…For example, natural small molecules, such as curcumin and congo red, have been reported to interact with the fibril-related conformation, and thus affect protein aggregation. 8 Artificial receptors, such as molecular tweezer, 9 cyclodextrin, 10,11 calixarene, 12 resorcinarene, 13,14 and cucurbituril, 15 have been designed to bind with one or several certain amino acids and inhibit the fibrillation of proteins. Certain peptides, either designed directly based on the Aβ sequence or designed without relying on the sequence, may also be utilized as inhibitors to interfere with the formation of fibrils or disrupt the aggregation process.…”
Section: Introductionmentioning
confidence: 99%